2014
DOI: 10.3389/fmicb.2014.00452
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells: key players in human herpesvirus 8 infection and pathogenesis

Abstract: Human herpesvirus 8 (HHV-8; Kaposi's sarcoma-associated herpesvirus) is an oncogenic gammaherpesvirus that primarily infects cells of the immune and vascular systems. HHV-8 interacts with and targets professional antigen presenting cells and influences their function. Infection alters the maturation, antigen presentation, and immune activation capabilities of certain dendritic cells (DC) despite non-robust lytic replication in these cells. DC sustains a low level of antiviral functionality during HHV-8 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 118 publications
3
21
0
Order By: Relevance
“…22 Dendritic cells play an important role in HHV8 infection and pathogenesis. 23,24 Myeloid-dendritic cells and macrophages can be infected by HHV8 through DC-SIGN receptor 25 and follicular dendriticlike cells have shown to express DC-SIGN. 26…”
Section: Discussionmentioning
confidence: 99%
“…22 Dendritic cells play an important role in HHV8 infection and pathogenesis. 23,24 Myeloid-dendritic cells and macrophages can be infected by HHV8 through DC-SIGN receptor 25 and follicular dendriticlike cells have shown to express DC-SIGN. 26…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with a previous study from our laboratory reporting that HHV-8 skews the cytokine response of infected dendritic cells to a Th2 response. 19,20 The cytokine profile of HHV-8 seropositive men (among the cancer controls) represents a pro-inflammatory without killing immune response, which is favorable for maintenance of viral latency.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Previous studies by ours and other's laboratories have reported that KSHV infects DCs or their monocyte precursors in vivo 40 or in vitro, resulting in a reduction of their immune functions or in an inhibition of monocyte differentiation. [41][42][43][44][45][46] In this study, we investigated whether KSHV infection of THP-1 monocytoid cells or primary monocytes could interfere with their autophagic process induced by several stimuli and be the underlying mechanism leading to their impaired in vitro differentiation.…”
Section: Introductionmentioning
confidence: 99%